Analisis Kesalahan Morfologi dalam Berita Online pada Website IDN Times - Erfina Rahayu; Fadhilatur Rosyidah; Nadia Putri Nabhila; Icha Fadhilasari; Arisni Kholifatu Amalia Shofiani5 (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2024)
IDN Times is an Indonesian digital media platform aimed at the younger generation. IDN Times is a journalistic company with two main offices in Jakarta and Surabaya. As a media outlet disseminating news to its readers, IDN Times is not free from language errors in creating and distributing news. The aim of this research is to explain the types of morphological language errors in news writing on IDN Times concerning corruption and the viral fake calculator in the film "In-laws Are Deadly." The researcher focuses the investigation on news published in June. This research is descriptive qualitative in nature. The method used in this research are reading and writing. The results of the study show the presence of language errors in the field of morphology, which include: 1) Errors in affixation omission, and 2) Errors in word writing. This analysis is expected to serve as an evaluation to be more careful in writing news, particularly in the aspect of morphology.